IMPLEMENTATION OF OUTPATIENT FAMILY PLANNING INFORMATION SYSTEM WITH WATERFALL - Octaviana, Vina; Syahidin, Yuda; Sari, Irda; Sukmawijaya, Jeri (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Population growth in some regions such as Asia is still high, especially in the number of births in children. Indonesia is one of the many countries whose birth rate growth is still high. With this high birth rate, it will cause problems for the region such as the problem of uncontrolled population growth if the birth rate continues to be high in addition to the social and economic impact of the region. To reduce the birth rate, the government created a family planning program to minimize the high birth rate. In birth control with this birth control program, contraceptive devices and drugs (ALOKON) are used as a prevention of pregnancy. This is intended to determine the level of allocone use in family planning patients in the outpatient unit and recap reports of birth control patients in the outpatient unit. In addition, the era of digitalization of technology utilization with information systems that have been increasingly developed and advanced, especially in the health sector. The system development method used in this journal is the waterfall method which consists of analysis, system design, implementation, unit testing, and maintenance. The results obtained are in the form of developing implementation results from the design made into a family planning information system in the outpatient unit. This research was made to develop an existing information system and can assist medical record officers in processing data and reports more effectively and efficiently. Keywords: alokon; growth of birth rate; information system; kb  Abstrak: Pertumbuhan penduduk dibeberapa wilayah seperti di Asia masih tinggi terutama pada angka kelahiran pada anak. Indonesia merupakan salah satu dari sekian banyak negara yang pertumbuhan angka kelahirannya masih tinggi. Dengan tingginya angka pertumbuhan kelahiran ini akan menimbulkan masalah bagi wilayah itu seperti permasalahan pertumbuhan penduduk yang tidak terkendali jika angka kelahiran terus tinggi selain itu berdampak pada kehidupan social dan ekonomi wilayah itu. Untuk menekan angka kelahiran pemerintah membuat program KB (Keluarga Berencana) dalam meminimalisir angka kelahiran yang tinggi. Dalam pengendalian kelahiran dengan program KB ini digunakan alat dan obat kontrasepsi (ALOKON) sebagai pencegah kehamilan. Hal ini ditujukan untuk mengetahui tingkat pemakaian alokon pada pasien KB di unit rawat jalan serta rekapan laporan pasien KB di unit rawat jalan tersebut. Selain itu era digitalisasi pemanfaatan teknologi dengan sistem informasi yang sudah semakin berkembang dan maju, terutama pada bidang Kesehatan. Metode pengembangan sistem yang digunakna pada jurnal ini adalah metode waterfall yang terdiri dari analisis, perancangan system, implementasi, pengujian unit, dan pemeliharaan. Hasil yang diperoleh berupa pengembangan hasil implementasi dari perancangan yang dibuat menjadi system informasi KB di unit rawat jalan. Penelitian ini dibuat untuk mengembangkan system informasi yang telah ada serta dapat membantu petugas rekam medis dalam pengolahan data dan laporan yang lebih efektif dan efisien. Kata kunci: alokon; kb; pertumbuhan angka kelahiran; sistem informasi